Development of novel Nafion/Meso-silicon-oxide membranes doped with phosphotungstic acid for high temperature proton exchange membrane fuel cells - Hu, Andy Jianwei. (2010)
The increasing rate of depletion of fossil fuels and pollution has led to an increasing demand for alternative energy sources and more efficient energy conversion methods. Fuel cell is a kind of electrochemical device that converts chemical energy of fuels to electrical energy directly.